Soil phenolic compound variability in two Mediterranean olive groves - Grilli, Eleonora; Di Resta, Esterina; Scognamiglio, Monica; Pacifico, Severina; Fiorentino, Antonio; Rodrigues Nogueira, Thiago Assis [UNESP]; Vigliotti, Renata Concetta; Ganga, Antonio (Czech Academy Agricultural Sciences, 2020)
Phenolic compounds (PCs) - with special reference to secondary plant metabolites - were characterised in two Mediterranean olive groves (Olea europaea L.). Representative pedological profiles were dug to identify and characterise the pedotype. Qualitative and quantitative analyses were carried out on soil core samples gathered at fixed depths (0-20 cm and 20-40 cm) and olive leaf methanol extracts by high-performance liquid chromatography with ultraviolet detection. The total PCs content reflected the soil organic carbon distribution, especially carbon of humic and fulvic acids, corroborating their crucial role in humification pathways. Among the analysed plant secondary metabolites, luteolin-4'-O-glucoside and verbascoside were the most abundant in leaves and soils, respectively. Most of the easily hydrolysed/metabolised phenols were not found in soils. Rutin and verbascoside, despite containing glucose, strongly persisted in the soil environment, probably due to their allelopathic effect. Oleuropein was not found in soils because it is highly soluble and mobile in the soil environment. Furthermore, the presence of clay in soil seemed to determine the accumulation of specific PCs. Our data suggest that PCs persistence in soil seems to be mainly determined by a balance between physicochemical and biochemical instability and allelopathic stability rather than their abundance in the plant.
Keywords: total phenols; water-soluble phenols; soil-olive system; flavonoid; degradation